Psychological Warfare Methods in the Light of the Holy Quran and Their Impact on the Individual and Society - موسى, أسماء محمد يعرب (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The Qur'an is God's revealed book, the eternal miracle of the Prophet, and a constitution organizing all aspects of human life. It addresses psychological warfare through verses warning against lying, falsehood, and deception, offering a complete framework for facing psychological challenges. Analysing these verses allows for a deeper understanding of this phenomenon and how to confront it based on Islamic principles, which laid the foundations for war, including self-defence and jihad through one's person, wealth, and tongue. Today, the "tongue" (media/propaganda) is among the most dangerous types of war. Its danger lies in its diverse methods of controlling minds, being a war of ideas aimed at changing convictions and casting doubt on beliefs. Its weapons are hidden under the guise of entertainment, culture, and science, aiming to destroy the foundations of any civilization. It has become the primary weapon for states to achieve goals with minimal losses. Psychological warfare, which aims to influence individuals and societies through rumours and misinformation, poses a significant challenge. Research Importance: 1. Understanding enemy strategies to undermine morale. 2. Enhancing a state's ability to counter misinformation and rumours, and understanding how to shape public opinion. 3. Including the ethical and legal dimensions of this warfare. 4. Helping formulate international laws to regulate its use and studying the impact of modern technology and social media. 5. Developing new techniques to detect and combat psychological campaigns. 6. Essential for strengthening national defensive/offensive capabilities and ensuring stability. Research Objectives: To clarify the concept, methods, and effects of psychological warfare. This research focuses on studying psychological warfare—its causes, objectives, methods, and effects—relying on Qur'anic methodology and inductive analysis to derive lessons for a deeper understanding of its impact on the individual and society in the modern age. Research Structure: · Chapter 1: Definition and Concept of Psychological Warfare. · Chapter 2: Methods of Psychological Warfare in the Qur'an (those used against Muslims and those used by Muslims). Chapter 3: Positive and Negative Effects of Psychological Warfare on the Individual and Society. The conclusion will include the research findings and recommendations.